PENGARUH HARGA TERHADAP MINAT BELI BELANJA DARING (ONLINE SHOPPING) PADA GENERASI Y STUDI KASUS: ALUMNI FISIKA ITB 2009 - Nurhakim, Rahman (JURNAL LENTERA AKUNTANSI, 2023)
This study aims to determine the relationship and influence between price and purchase intention on online purchases among millennials. This research was conducted using a survey sampling method using an intentional sampling technique as long as they have made purchases online and are millennials. The results of the research are hypothesis testing, definitive analysis and simple linear regression analysis using the IBM SPSS 25 tool. The results show that the price variable has a positive and significant effect on online buying interest. The correlation between the price variable and the online purchase intention variable is moderate and has a positive effect. Determination of the price variable on buying interest in online purchases is 19.8%, the rest is influenced by other factors not included in this study.Keywords: Price, Interest to Buy Online, Generation Y